2021
DOI: 10.3390/plants10091936
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Linearthin and Other Chalcone Derivatives from Aspalathus linearis (Rooibos) against UVB Induced Oxidative Stress and Toxicity in Human Skin Cells

Abstract: Skin cells suffer continuous damage from chronic exposure to ultraviolet light (UV) that may result in UV-induced oxidative stress and skin thinning. This has necessitated the formulation of cosmeceutical products rich in natural antioxidants and free radical scavengers. Aspalathus linearis (rooibos) is an endemic South African fynbos plant growing naturally in the Western Cape region. The plant is rich in phenolics and other bioactives with a wide spectrum of health benefits. The chemical study of an acetonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…In continuation of the previous studies to probe the involvement of isolated compounds from plant extracts in the phytomediated synthesis of metallic nanoparticles [17][18][19], green rooibos (GR) and ASP have been selected as reducing and stabilising agents in this study because of their wide spectrum of biological activities and antioxidant potential. The isolation procedures of pure ASP (Figure 1) and its spectroscopic data has been reported recently [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In continuation of the previous studies to probe the involvement of isolated compounds from plant extracts in the phytomediated synthesis of metallic nanoparticles [17][18][19], green rooibos (GR) and ASP have been selected as reducing and stabilising agents in this study because of their wide spectrum of biological activities and antioxidant potential. The isolation procedures of pure ASP (Figure 1) and its spectroscopic data has been reported recently [20].…”
Section: Resultsmentioning
confidence: 99%
“…this study because of their wide spectrum of biological activities and antioxidant potential. The isolation procedures of pure ASP (Figure 1) and its spectroscopic data has been reported recently [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…196 Other researchers have also reported high concentrations of luteolin-7-glucoside, isovitexin, as well as nothofagin, aspalalinin and linearthin, three rooibos-specific polyphenols, the last two of which are dihydrochalcones. 198,199 Aspalathin, the main flavonoid in unfermented leaves and stems, undergoes oxidation during the fermentation process, transforming into dihydro-iso-orientin. Similarly, nothofagin, structurally related to aspalathin, is present in significant concentrations in unfermented rooibos tea.…”
Section: Aromatic Leaf Beveragesmentioning
confidence: 99%
“…One study demonstrated that aspalathin, linearthin and nothofagin possess protective activity against UVB-induced oxidative stress and toxicity in human skin cells. 199 Moreover, aspalathin and linearthin also display the ability to protect SH-SY5Y cells against MPP + -induced neuronal toxicity. 201 Furthermore, aspalathin can ameliorate hyperglycemia-induced cardiomyocyte damage in vitro .…”
Section: Leafy Beverages (Lb)mentioning
confidence: 99%